Effectiveness of Acceptance and Commitment Training on Self-Worth and the Psychological Capital among Children of Divorce - Abbas Sadeghian; Mohammad-Kazem Fakhri; Ramezan Hasanzadeh (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: The population of children of divorce is increasing nowadays as divorce rates increase and the problems and issues arising from divorce at this evolutionary stage can greatly affect their self-esteem and their psychological capital. The purpose of this study was to investigate acceptance and commitment training on self-worth and psychological capital among children of divorce who who were under maternal custody. Materials and Methods: This research was of semi-experimental design with pretest-posttest and control group. The statistical population of this study included all adolescents who were under maternal custody and were studying in high schools of the city of Sari in the academic year of 2017-2018. A sample of 60 students were selected through multistage cluster sampling and randomly assigned to two experimental and control groups, each group including 30 participants. The experimental group participated in eight sessions of acceptance and commitment training sessions, while the control group did not receive any training. In order to measure the dependent variables, Luthanese psychological capital questionnaire and Nemati's Responsibility questionnaire were used. Multivariate analysis of covariance analysis was used to analyze the data in SPSS software version 22. Results: The mean (SD) age of the participants in the experimental group was 16.2 (5.3) and the control group 16.7 (6.3). The mean (SD) cognitive capital of the experimental group was 85.4 (13.8) in the pretest, which increased to 99.3 (16.7) post-test (P<0.01); however, the mean (SD) cognitive capital of the control group was 85.6 (12.9) in the pretest, and 86.4 (14.2) in post-test, which was not statistically significant. The mean (SD) self-worth score of the experimental group was 12.49 (17.6) in the pretest, which increased to 167.2 (22.1) post-test (P <0.01); however, the mean (SD) self-worth score in the control group was 123.8 (16.4) in the pretest, 125 (17.9) in the post-test, which was not statistically significant. Conclusion: The findings of this study showed acceptance and commitment training can be an appropriate interventional method for improving self-worth and psychological capital among children of divorce. DOI: http://doi.org/10.22037/ch.v6i3.24825